Radiological and Histopathological Features of Internal Tooth Resorption - KOEHNE, TILL (In Vivo, 2020)
Background: Internal root resorption is an endodontic disease characterized by progressive resorption of dentin from the inside of the pulp chamber. It is a comparatively rare finding in the permanent dentition, and the underlying pathology is not fully understood. Case Report: A 45-year-old patient was referred to our Department for the evaluation of the lower right canine and the upper left wisdom tooth. Pulp sensitivity tests, cone-beam tomography, and magnetic resonance imaging were used to determine the extent of lesions of the affected teeth. The teeth were subsequently extracted due the extent of the lesions. The same was the case for the upper right canine, which developed a severe internal resorption 10 months later. Micro-computed tomography of the extracted teeth revealed that all lesions had a well-defined border with no evidence of sclerosis or hypomineralization. Pulp stones were evident inside the pulp chamber. Ground sectioning of the upper right canine revealed pulp necrosis and an acute infection that had gradually moved in the apical direction. Large multi-nucleated resorbing cells were found on the dentin surface. Importantly, the apical half of the pulp exhibited comparatively normal tissue without substantial inflammatory changes. Decalcified histology of the upper left wisdom tooth demonstrated a completely different histopathological appearance characterized by chronically inflamed granulation tissue with pseudoepitheliomatous hyperplasia and massive bacterial colonization. Conclusion: Our analyses demonstrate that internal root resorption is a multifaceted dental disease with considerable variability in the rate of the underlying inflammatory changes. Oral surgeons should take this into consideration when evaluating the need for extraction of teeth with internal root resorption.